Contestation of Rhetoric within the Chinese Tradition: An Overview of Confucian Moralistic Rhetoric, Daoist Transcendental Rhetoric, and Mohist Utilitarian Rhetoric. Issue 2 (4th May 2019) - Lu, Xing
ABSTRACT: This paper reviews and compares diverse rhetorical conceptualizations within Chinese rhetorical tradition during the fifth to third century B.C.E. Textual evidence shows that three schools of thoughts, namely Confucianism, Daoism, and Mohism, have contested with and challenged one another on the components and functions of rhetoric. Confucianism is more concerned with the moral character of the speaker while Mohism claims that rhetoric is used for mutual benefit and contains a rational element. Daoism, on the other hand, approaches rhetoric with a transcendental and dialectical outlook. This overview demonstrates the multi-faceted characteristics of ancient Chinese rhetoric.